2007
DOI: 10.1007/s11267-006-9107-5
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Acidified Streams in Forests Treated by Total Catchment Liming

Abstract: Reduced emissions of acidifying pollutants have changed the acidification process, and as a result, forest soils and surface waters are slowly recovering in Sweden. However, model calculations show that some areas may never recover completely unless further measures, such as liming, are undertaken. Liming of surface waters (lakes, rivers and wetlands) has been successfully practised in Sweden since the 1970s, but repeated treatments are necessary. A full recovery of acidified lakes and streams without frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…According to a recent metaanalysis (of predominantly European and North American studies), biomass harvesting can lower the pH and base saturation of surface soils and reduce concentrations of foliar calcium in the regenerating stand, but only when foliage is removed along with tree stems and branches (Achat et al 2015). Research has shown that applications of wood ash can be used to increase soil pH and base saturation, thereby increasing surface water pH, which, in turn, may facilitate the ecological recovery of surface waters (Westling and Zetterberg 2007;Johansson 2014;Huotari et al 2015).…”
Section: To Counteract the Acidifying Effects Of Atmospheric Depositimentioning
confidence: 99%
“…According to a recent metaanalysis (of predominantly European and North American studies), biomass harvesting can lower the pH and base saturation of surface soils and reduce concentrations of foliar calcium in the regenerating stand, but only when foliage is removed along with tree stems and branches (Achat et al 2015). Research has shown that applications of wood ash can be used to increase soil pH and base saturation, thereby increasing surface water pH, which, in turn, may facilitate the ecological recovery of surface waters (Westling and Zetterberg 2007;Johansson 2014;Huotari et al 2015).…”
Section: To Counteract the Acidifying Effects Of Atmospheric Depositimentioning
confidence: 99%
“…Liming generally improves the forest nutrition in Ca and Mg (Bonneau et al, 1992;Huettl and Zoettl, 1993) by (i) delivering plant-available Ca and Mg (Wilmot et al, 1996;Moore et al, 2000;Bridgham and Richardson, 2003), and/or (ii) because liming improves humus mineralization (Bridgham and Richardson, 2003;Piatek et al, 2009), which increases the nutrient concentration of soil solution, and/or (iii) because liming raises pH and base saturation and decreases Al toxicity to roots (Cronan et al, 1989;De Wit et al, 2010). The rate and depth of Ca and Mg penetration in soil depends on lime solubility (Hindar, 2005;Westling and Zetterberg, 2007), on climate, and on physical, chemical, and biological soil properties, which are in turn influenced by liming. At the catchment level, the effects of liming on stream water chemistry vary with the proportion of catchment limed (Dalziel et al, 1994;Hindar et al, 2003), soil acidity and buffering capacity (Hindar, 2005;Lofgren et al, 2009), and catchment hydrology (Brahmer, 1994).…”
Section: Introductionmentioning
confidence: 99%